The diagnosis and treatment of testicular torsion in children with non-scrotal initial symptoms - Mao, Chang-Kun; Cao, Yong-Sheng; Liu, Xiang; Peng, Bo; Chu, Han; Deng, Qi-Fei; Yu, Xin; Tao, Cheng-Pin; Zhang, Tao; Yang, Chao; Peng, Shan (Frontiers in Pediatrics, 2023)
Objective: To explore the clinical characteristics of testicular torsion in children with non-scrotal initial symptoms who were misdiagnosed, in order to improve understanding of this disease. Methods: A retrospective analysis was conducted on 73 cases of testicular torsion in children admitted to our department from October 2013 to December 2021. According to the diagnostic and treatment status of the children, they were divided into a misdiagnosis group with non-scrotal initial symptoms (27 cases) and a group with a clear diagnosis at first visit (46 cases). Clinical data including the age at surgery, clinical presentations, physical examination, number of visits (≥2 times), affected side, time from onset of initial symptoms to surgery and operation outcomes were collected. The TWIST (Testicular Workup for Ischemia and Suspected Torsion) score was calculated and analyzed according to the symptoms and signs of these patients. Results：A total of 73 patients were included in our study underwent emergency surgical exploration in our department.There were statistical differences between the two groups in time from onset of initial symptoms to surgery, number of visits, degree of testicular torsion, and the rate of orchiectomy (P<0.05). There were no statistically differences (P>0.05) in age, affected side, TWIST score, guardian, direction of testicular torsion, intra-vaginal or extra-vaginal torsion, and Arda classification. The postoperative follow-up was 6-40 months, 36 cases of orchiopexy resulted in testicular atrophy in one patient after six months, two patients lost to follow-up, and the remaining 33 cases developed well. The contralateral testis of 37 children with orchiectomy developed normally without torsion. Conclusions：The clinical manifestations of testicular torsion in children are diverse and can easy lead to misdiagnosis. Guardians should be aware of the disease and seek timely medical attention. When initial diagnosis and treatment by first doctor is difficult, TWIST score evaluation during physical examination may be useful, especially for patients with intermediate-to-high risk scores. Combining color Doppler ultrasound examination can assist in diagnosis, and surgery should be performed immediately when testicular torsion is suspected.